Analysis of the mineralogical characterization of copper porphyries as a support for flotation processes - Iriarte Dávila, Guillermo Kenneth (2022)
The mining industry of porphyry copper deposits process complex and low-grade minerals (Romero Toledo et al., 2017). One of the problems related to this practice, is the type of mineral, harming the mining - metallurgical treatment that affects the consumption of excessive energy and the critical recovery of economic minerals (Mudd, 2010). The objective of the research was to analyze the mineralogical characterization; then to contrast the behavior of the minerals in the process of flotation of minerals in the porphyry deposits of copper and with it to implement improvements (Díaz Villena, 2017). The techniques used were X-ray diffraction, optical-electronic microscopy (Manzaneda Cabala, 2010) and chemical analysis. They provided reliability and support to determine qualitatively and quantitatively the mineral phases that cause problems in the flotation of copper minerals  (Donoso Droguett, 2020). The main conclusion is that mineralogical characterization encompasses activities that utilize a better understanding of the properties of the ore and residues, which impact positively or negatively on the value of the product.